Effect of subthalamic deep brain stimulation on gait in patients with advanced Parkinson’s disease - Juan F. Mier-García; Lina M. Villegas-Trujillo; Juan Camilo Salcedo; Sebastián Ordoñez; María José Uparela; Fernanda Arbeláez; Camilo A. Turriago-Pérez; Lesbby Gómez-Salazar; Óscar A. Escobar-Vidarte (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Advanced Parkinson's disease severely affects gait. According to literature, deep brain stimulation of the subthalamic nucleus has scarce impact on gait in this disease.